ANALISIS PENGARUH EKUITAS MEREK TERHADAP MINAT BELI ULANG KONSUMEN (STUDI PADA PRODUK PERAWATAN WAJAH MEREK ERHA DI PONTIANAK - YUDI, PUSPITA SARI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Long-term success of a brand is the emergence of repurchase intention from the customers. In the process of purchasing, consumers have a tendency to choose a product with strong brand equity because they think the product has a high quality. Erha is a brand that is managed by PT. Erha Clinic Indonesia, which has expanded its market in Pontianak since 2010. This research is an associative study which aims to determine the effect of brand equity dimensions outlined in brand awareness, brand associations, perceived quality, and brand loyalty towards repurchase intention. The research was conducted by survey respondents using a questionnaire containing the measurement indicators for the variable brand awareness, brand associations, perceived quality, brand loyalty, and repurchase intention. Using technique quotas sampling, as many as 145 respondents were included in this research. The population in this research is Erha customers in Pontianak with the inclusion criteria of the sex women from 12 to 56 years old who have bought skin care products more than once. The data obtained from the questionnaire were analyzed using descriptive analysis and multiple linear regression analysis. The results showed that brand awareness, brand associations, perceived quality, and brand loyalty have a significant influence on repurchase intention either simultaneously or partially. Based on the analysis, the highest impact on repurchase intention refers to perceived quality by 24.6% (p 0.05). The other variables are brand awareness, brand associations, and brand loyalty has influence on repurchase intention respectively by 3.9%, 23.9%, and 11.8%. R-square values obtained in this study was 0.558, indicating that the contribution of brand awareness, brand associations, perceived quality, and brand loyalty to repurchase intention is at 55.8%, the rest is influenced by other variables that do not exist in this research.